New Trends in Migraine Pharmacology: Targeting Calcitonin Gene–Related Peptide (CGRP) With Monoclonal Antibodies - Scuteri, Damiana; Adornetto, Annagrazia; Rombolà, Laura; Naturale, Maria Diana; Morrone, Luigi Antonio; Bagetta, Giacinto; Tonin, Paolo; Corasaniti, Maria Tiziana (Frontiers in Pharmacology, 2019)
Migraine is a common neurologic disorder characterized by attacks consisting of unilateral, throbbing headache accompanied by photophobia, phonophobia and nausea which remarkably reduces the patients’ quality of life. Not migraine-specific nonsteroidal anti-inflammatory drugs (NSAIDs) are effective in patients affected by mild episodic migraine whilst in moderate or severe episodic migraine and in chronic migraineurs triptans and preventative therapies are needed. Since these treatments are endowed with serious side effects and have limited effectiveness new pharmacological approaches have been investigated. The demonstrated pivotal role of calcitonin gene-related peptide (CGRP) has fostered the development of CGRP antagonists, unfortunately endowed with liver toxicity, and monoclonal antibodies (mAbs) towards circulating CGRP released during migraine attack or targeting its receptor. Currently, four mAbs, eptinezumab, fremanezumab, galcanezumab for CGRP and erenumab for CGRP canonical receptor, have been studied in clinical trials for episodic and chronic migraine. Apart from the proven effectiveness, these antibodies have resulted well tolerated and could improve the compliance of the patients due to their long half-lives allowing less frequent administrations. This study aims at investigating the still poorly clear pathogenesis of migraine and the potential role of anti-CGRP mAbs in the scenario of prophylaxis of migraine.